Research Progress of Isoquinoline Alkaloids against Liver Cancer Based on Network Pharmacology and Literature - SUN Xing-qian; CAI Jun-fei; GAO Jia-ju; PU juan; MA Yun-shu (Liang you shipin ke-ji, 2021)
To explore the anti-hepatocellular mechanism of five kinds of isoquinoline alkaloids， with the help of TCMSP， string， venny database and WebGestalt online analysis software to obtain the target and perform protein interaction network (PPI)， gene ontology (GO)， gene interaction (KEGG) function enrichment analysis， and use Cytoscape software to construct the network. At the same time， berberine in proberberine，Tetrandrine in dibenzyl alkaloids， sanguinarine in Phenphenanthroline， sinomenine in morphine and lycopine in pyrrolidine were obtained by literature review， induction， sorting and analysis. According to the structural mechanism of action， the potential of each type of representative isoquinoline alkaloid in the treatment of liver cancer and the mechanism of anti-liver cancer were expounded. Five active ingredients were screened and 52 targets such as p53 (tumor suppressor gene)， NCOA2 (nuclear receptor co-activator 2)， IL-2(interleukin 2) were obtained which mainly involved calcium ion signaling pathway， estrogen receptor signaling Pathways and PI3K/Akt signaling pathways. Through network pharmacology and literature collection， it is confirmed that isoquinoline alkaloids may be involved in the regulation of PI3K-Akt pathway，etc.， and can have therapeutic effects on liver cancer through multiple targets and multiple pathways. This paper can provide reference and basis for further clinical research on the anti-liver cancer effect of isoquinoline alkaloids.